Parametric study and efficiency optimization of the solar coupled hybrid micro gas turbine power plant for high altitude flight. (August 2019) - Thomas Jayachandran, A V; Gangisetty, G; Tkachenko, A; Rybakov, Viktor
Abstract: The performance and feasibility study of a hybrid system designed by combining solar micro gas turbine for power generation process during high altitude flight were explored. The high altitude flight could be defined as long duration stratosphere balloon. Payloads in this high altitude balloon flight could be remote sensing satellites or communication satellites which require a continuous high-density power supply that cannot be provided by solar panels. To reduce greenhouse gas emission, the hybrid method was chosen and studied for its effectiveness in a gas turbine power plant. A thermodynamic cycle analysis for high altitude gas turbine power generator was analyzed along with various power conversion systems and recuperator placement configurations were investigated. The working parameters such as Overall Pressure Ratio and Turbine inlet temperature was investigated with the thermo gas dynamic calculation for designing an optimized power plant. Parametric optimization for determining the realistic and practical combination of recuperators for improving the specific fuel consumption and overall efficiency of the Micro gas turbine power plant was performed. The recuperators could be positioned either in the exhaust of a high-pressure turbine or at the exhaust of the free turbine. The recuperator position and heat extraction are explored and the resulting data depicts the recuperator surface area increases the effectiveness thus the fuel consumption decreases but the recuperator increases the overall mass and volume of the power plant size. A comprisable trade-off was made between the recuperator performance and its size and the results are optimized for high overall efficiency of the power plant. A short trade-off between the selected system and existing systems were made. The system performance, Efficiency optimization and the component size and weight characteristics were performed to deliver maximum payload capabilities.